Coherent learning control of vibrational motion in room temperature molecular gases - Murnane, M. M., author; Kapteyn, H. C., author; Rabitz, H., author; Geremia, J. M., author; Pearson, B., author; Bucksbaum, P. H., author; Backus, S., author; Bartels, R. A., author; Weinacht, T. C., author; Elsevier Science B. V., publisher (Colorado State University. Libraries, 2001)
An evolutionary learning algorithm in conjunction with an ultrafast optical pulse shaper was used to control vibrational motion in molecular gases at room temperature and high pressures. We demonstrate mode suppression and enhancement in sulfur hexafluoride and mode selective excitation in carbon dioxide. Analysis of optimized pulses discovered by the algorithm has allowed for an understanding of the control mechanism.